The non-intuitive, in-vivo behavior of aponeuroses in a unipennate muscle - Bossuyt, F. M.; Abramovic, S.; Leonard, T.; Sawatsky, A.; Smith, C. R.; Taylor ,W. R.; Scott, W. M.; Herzog, W. (Journal of Biomechanics, 2023)
Experimental observations and theoretical models suggest that the loading of muscular aponeuroses is complex, causing strain patterns that are not reconcilable with the frequently assumed mechanical "in series" arrangement of aponeuroses with muscles and tendons. The purpose of this work was to measure the in-vivo longitudinal strains of the distal and proximal aponeuroses and force of the unipennate Medial Gastrocnemius (MG) muscle during locomotor activities. Sonomicrometry crystals and a force buckle transducer were implanted to measure aponeurosis strains and MG forces in the left hindlimb of four healthy female sheep while walking at different speeds and inclination angles on a motorized treadmill. The resulting aponeurosis strains versus the corresponding muscle forces resulted in a complex interaction that is not reconcilable with a mechanical "in series" arrangement of aponeuroses with either the free tendon or muscle, as has frequently been assumed when trying to determine the storage and release of mechanical energy in muscles or the stiffness and elastic modulus of in-vivo aponeurosis tissues. We conclude that the interaction of muscle tissue with aponeuroses in the sheep MG allows for elongation of the aponeuroses at low forces in the passive muscle, while elongation in the active muscle is greatly reduced possibly due to the complex shear forces and pressures produced when the muscle is activated. It is likely that the observed aponeurosis mechanics are similar in other unipennate skeletal muscles, but the current study was limited to a single muscle and therefore does not allow for such extrapolation at this time.